Dynamic modelling of induction motor based on rotor reference frame / Nurani Sah Zakaria - Zakaria, Nurani Sah (2011)
Induction machine is strong non-linear element, in which the electrical and mechanical transient process is independent. Induction machine has a stator and a rotor mounted in bearing and separated from the stator by an air-gap. It also can operate both as motor and generator. Induction motor are widely used, especially poly-phase induction motor, which are frequently used in industrial drives. But it is a multi variable, strong-coupling nonlinear system. Variable speed drives are converter-fed from finite source, unlike the utility sources due to the limitations of the switch rating and filter sizes. This will result in their incapability to supply large transient power. Most efficient induction motor will have steady-state in shortest time to achieve steady state which means can operate with frill efficiency in shortest time. In order to predict or measure the dynamic behavior of induction machine; the dynamic simulation is one of the key steps in validation of the design process of the motor drive systems, eliminating incompatible design mistakes and resulting errors in the prototype construction and testing. In order to do dynamic simulations, MATLAB program implemented to complete the step referring to reference frames. The objective of this project is to develop a dynamic mathematical model of a three-phase induction motor for purpose of performing simulation study and develop MATLAB programming simulation of the induction three-phase motor model to compared it with theoretical. The model is derived using rotor reference frame approach using MATLAB programming. A Runge-Kutta fourth order numerical method is used to solve the induction motor voltage differential equations. The obtained simulation results are compared with known results to determine the reliability of the developed model. Evaluation of the comparisons revealed that the developed model is reliable for use in performing dynamic simulation of three phase induction motor.